Panel Analysis on the Effect of Government Expenditure on Education and Health Sector against Poverty Numbers in Aceh 2010-2015 (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this research is to know the effect of government expenditure on education and health sector, the difference of districts with the city and the difference of parent regions to the poverty rate in Aceh Province. The method used in this study is the analysis with secondary data period 2010-2015. The Chow test yields the conclusion that the exact model used is the Common Effect Model. The estimation results indicate that the education budget, the urban area significantly influences the poverty rate, while the health budget and the district / city expansion have no effect on the poverty reduction. The simulation results concluded that if the education budget is budgeted 20 percent of the total Regional Revenue and Expenditure Budget ( APBD) and the health budget is realized by 10 percent of the total APBD budget it will be able to reduce poverty in Aceh Province on average by 0.55 percent per year. Regency / municipality governments are expected to realize the education budget of 20% of APBD in accordance with Law no. 20 of 2003 article 49 paragraph 1 of the National Education System and the health budget of 10% of APBD in accordance with Law No.36 of 2009 article 171 paragraph 2 on Health.